THE ANALYSIS OF EFL LEARNING STRATEGY OF THE VISUALLY IMPAIRED JUNIOR HIGH SCHOOL STUDENTS - Setyawati N.M.Y.; Adnyani L.D.S.; Piscayanti K.S. (Universitas Pendidikan Ganesha, 2018)
This study aimed to describe about the learning strategies that the visually impaired students (VIS) used in learning EFL as what explained by Oxford (2005) that during a learning process, strategies used by the learners depend on their motivation, background, age, learning style, achievement, and gender. It was found that there are 6 strategies used, they are (1) cognitive such as practicing, repeating, getting idea, analyzing and reasoning, summarizing and translating; (2) metacognitive, they are paying attention to the lesson and showing evidence of understanding; (3) social strategy, they are empathizing with others, asking questions, asking for a review, asking for additional input, and asking for confirmation; (4) affective, by decreasing their anxiety; (5) memory, by making associations, contextualizing words, recalling, resorting to visual residue, wrapping up, and retaking previous ideas; (6) compensation, by overcoming limitations in speaking and writing, attempting to give an answer, and using language mixing. Thus, visually impaired students must be treated special to cover their needs with appropriate teaching strategies and facilities.